Tteokbokki Jjang / Mohamad Zulkhairy Shuhaimi ... [et al.] - Shuhaimi, Mohamad Zulkhairy; Razlan, Muhamad Zahiruddin Muhamad Zahiruddin; Ahmad Kamil, Muhammad Ady Irfan; Mohammad Yani, Muhammad Aiman Marzuqi (2021)
Our business is formed based on partnership between five partners who are earnestly attempting to produce halal Korean food restaurants in Permatang Pauh in order to fulfil the needs and wants of Permatang Pauh citizens who are waiting for a Korean cuisine restaurant to be opened in Permatang Pauh. Our restaurant, “Tteokbokki Jjang” is named after a Korean phrase which means ‘the best tteokbokki (one of popular food in Korea)’ and is striving to satisfy our customers with delicious food and best customer service. In order to open our business, the partners contributed RM150,000 as starting capital. On the other hand, we will also apply for a loan from Maybank at the amount of RM 200,000. We will commence our business on 1st February 2020. Our vision is to be the number 1 halal Korean restaurant in Malaysia by 2022, while our mission is to serve halal and delicious food as well as high quality service to our customers. The motto of our restaurant is “Wanna Tteokbokki, Wanna One” which symbolizes our vision, to be the best and number 1 halal Korean restaurant in the future. Our business is located at C-09, Jalan Permatang Pauh, Kampung Belah Dua, 13500, Permatang Pauh, Pulau Pinang. Our contact number is 09-42358910 while our official website www.tteokbokkiiiang.com. “Tteokbokki Jjang” offers famous Korean food (rice cake) which is halal to serve the wants and needs of people in Permatang Pauh. It has been a trend for Malaysian especially youngsters, to eat Korean food. Recently, Korean food has already been widely accepted by Malaysians with the influx of Korean instant noodles called ramen into Malaysian markets. In that regard, we found the business opportunity of opening “Tteokbokki Jjang” Korean restaurant in Permatang Pauh to introduce the Korean culture to people in Permatang Pauh. Our target customers for this business opportunity are mainly students at the age range of 12- 25. In Permatang Pauh, there are various educational institutions such as UiTM, polytechnics and schools which definitely have students who love to follow the trend of eating Korean food. According to our survey towards the students, 95% of the respondents agreed if we open a Korean Restaurant at Permatang Pauh. Therefore, we are very sure that our restaurant will be able to excel in line with the rapid development of Permatang Pauh. In the future, we are planning to expand Business to other places such as Bertam and Bayan Lepas as well as other places outside Permatang Pauh throughout Malaysia. Moreover, we also want to vary our menus that follow Korean trends. Currently, we only promote tteokbokki as our main menu. Therefore, in the future, we will vary our menus to promote other Korean food